2023
DOI: 10.1039/d2sc05217b
|View full text |Cite
|
Sign up to set email alerts
|

Elastic organic semiconducting single crystals for durable all-flexible field-effect transistors: insights into the bending mechanism

Abstract: Although many examples of mechanically flexible crystals are currently known, their utility in all-flexible devices is not yet adequately demonstrated, despite their immense potential for fabricating high performance flexible devices....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…Such soft molecular crystals shatter the preconceived notion that crystals are brittle and hard and, when struck or bent with external force, they typically crack or shatter, inevitably. , The soft matter of organic single crystals responds to external force in a different manner: they show plastic or elastic deformation . These soft molecular crystals share properties of both crystals and soft matter, endowing them with great potential in mechanical actuators, optical devices, organic electronics, etc. The mechanical properties of molecular crystals strongly rely on the molecular packing arrangements and intermolecular interactions, which can be tailored by crystal engineering approaches. Designing new structures with the desired physical and chemical properties using advanced third-generation strategies of crystal engineering is an attractive and rapidly developing research area. , Much effort has been made to study the mechanism of flexible crystals and gain a deep understanding of mechanical compliance to a large extent. The importance of weak dispersive interactions has been acknowledged as it has a natural advantage in controlling local molecular movements, which is essential to ensure the effective dissipation of stresses generated from structural functions. Almost all of the key structures of mechanically flexible crystals exhibit a combination of weak intermolecular interactions such as van der Waals (vdW), weak hydrogen-bonding, , lighter halogen, ,, and π···π interactions. , Several recent studies reported unusual plastic crystals based on strong hydrogen bonding. , Strong hydrogen bonding was also found to play a nonnegligible role in elastic crystals of isosorbide 5-mononitrate and (2 S ,3 R )-3-ethyl-1-phenylhex-5ene-2,3-diol .…”
Section: Introductionmentioning
confidence: 99%
“…Such soft molecular crystals shatter the preconceived notion that crystals are brittle and hard and, when struck or bent with external force, they typically crack or shatter, inevitably. , The soft matter of organic single crystals responds to external force in a different manner: they show plastic or elastic deformation . These soft molecular crystals share properties of both crystals and soft matter, endowing them with great potential in mechanical actuators, optical devices, organic electronics, etc. The mechanical properties of molecular crystals strongly rely on the molecular packing arrangements and intermolecular interactions, which can be tailored by crystal engineering approaches. Designing new structures with the desired physical and chemical properties using advanced third-generation strategies of crystal engineering is an attractive and rapidly developing research area. , Much effort has been made to study the mechanism of flexible crystals and gain a deep understanding of mechanical compliance to a large extent. The importance of weak dispersive interactions has been acknowledged as it has a natural advantage in controlling local molecular movements, which is essential to ensure the effective dissipation of stresses generated from structural functions. Almost all of the key structures of mechanically flexible crystals exhibit a combination of weak intermolecular interactions such as van der Waals (vdW), weak hydrogen-bonding, , lighter halogen, ,, and π···π interactions. , Several recent studies reported unusual plastic crystals based on strong hydrogen bonding. , Strong hydrogen bonding was also found to play a nonnegligible role in elastic crystals of isosorbide 5-mononitrate and (2 S ,3 R )-3-ethyl-1-phenylhex-5ene-2,3-diol .…”
Section: Introductionmentioning
confidence: 99%
“…In organic π-conjugated molecules, exciton–polaritons (EPs) can be formed as a result of strong coupling between excitons and resonator photons. Because of the large exciton binding energies for organic molecules, EPs are formed, even at room temperature. Furthermore, polariton lasing, which is generally achieved by the Bose–Einstein condensation of EPs, has been recently demonstrated even in naturally formed crystal resonators. , Moreover, OWGs based on EP formation have also been reported . The realization of a flexible mechanism based on π–π interactions and a designed π-conjugated molecular structure has various potential applications.…”
mentioning
confidence: 99%
“…Furthermore, polariton lasing, which is generally achieved by the Bose−Einstein condensation of EPs, has been recently demonstrated even in naturally formed crystal resonators. 31,32 Moreover, OWGs based on EP formation have also been reported. 33 The realization of a flexible mechanism based on π−π interactions and a designed πconjugated molecular structure has various potential applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Though interesting insights into bending have been made from these model stimuli, there is no guarantee that this indirect information accurately reflects the structural response to bending, often leaving more questions than answers. Alternatively, a growing number of studies have directly probed the structure in bent MFCs, both at the bulk scale by, e.g., mechanical analysis and microscopy, and at the atomic scale by μ-focus analyses including Raman spectroscopy and X-ray diffraction. , Coupled with ab initio modeling efforts, ,, these studies have revealed exceptional new mechanistic insights into how mechanical flexibility is achieved, pointing toward new material design strategies.…”
mentioning
confidence: 99%